Non-COVID-19 uptake of personal protective equipment and rules compliance amongst industrial workers in Kano, Nigeria - Muhammad Garba Rayyan; Usman Muhammad Ibrahim; Usman Sunusi Usman; Karibullah Idris Muhammad (Nigerian Postgraduate Medical Journal, 2022)
Background: Every workplace has got hazards in many different forms, ranging from sharps, falling objects, chemicals, infections, noise and a lot of other potentially dangerous situations. The occupational safety and health administration mandates employers to protect their employees from such potentially dangerous workplace hazards. Personal protective equipment (PPE) plays an important role in preventing and ensuring health safety amongst industrial workers. This study aimed to determine the use of PPE and rules compliance amongst Industrial Workers in Kano State. Methods: A cross-sectional study design was used to assess 150 workers selected from the Sharada Industrial Estate, Kano, Nigeria, using a multistage sampling technique. Data were obtained using semi-structured interviewer-administered questionnaires and analysed using SPSS version 22.0. Results: The response rate was 88.2%, and the mean age of respondents was 28.1 ± 7.4. About 72% were male, 74.7% had secondary education and 16.4% reported ever having a child with a congenital anomaly. Up to 25% reported using PPE always, 62% used PPE occasionally and 12% never used PPE. Factors significantly associated with the use of PPE at bivariate level were: Gender, 'provision of statutory regulation by the management', 'provision of PPE on worksite' and 'provision of training to staff' respectively. However, on multivariable regression analysis, only 'provision of statutory regulation by the management' and 'provision of PPE on worksite' were found to be independent (intrinsic) predictors of the use of PPE. Conclusions: Training alone does not necessarily increase the uptake of PPE amongst industrial workers. There is a need to ensure the availability of PPE at the worksite, as well as statutory regulations by industries.